TLR2 Expression in Peripheral CD4+ T Cells Promotes Th17 Response and Is Associated with Disease Aggravation of Hepatitis B Virus-Related Acute-On-Chronic Liver Failure - Xu, Chunli; Lu, Yinping; Zheng, Xin; Feng, Xuemei; Yang, Xuecheng; Timm, Joerg; Wu, Jun; Wang, Baoju; Lu, Mengji; Yang, Dongliang; Liu, Jia (Frontiers in Immunology, 2017)
Th17 responses have been shown to play crucial roles in the pathogenesis of hepatitis B virus (HBV)-associated acute-on-chronic liver failure (ACLF). The mechanism underlying the enhanced Th17 responses in these patients remains largely unclear. Here we investigated TLRs expression in peripheral T cells and their roles in Th17 cell differentiation and disease aggravation in ACLF patients.18 healthy subjects (HS), 20 chronic HBV-infected (CHB) patients and 26 ACLF patients were enrolled and examined for TLRs expression in PBMCs. The correlations of T cell TLR2 expression with the antigen non-specific Th17 responses and disease aggravation, as well as the Th17 response to TLR2 ligand stimulation were evaluated in ACLF patients. Compared to HS and CHB patients, ACLF patients showed a distinct TLRs expression pattern in PBMCs. Significantly increased TLR2 expression in T cells was observed in ACLF patients. The TLR2 expression in CD4+ T cells was correlated with the Th17 responses and the clinical markers for disease aggravation in ACLF patients. Moreover, TLR2 ligands stimulation promoted Th17 cell differentiation and response in PBMCs of ACLF patients. These findings implicate TLR2 signaling plays critical roles in Th17 cell differentiation and disease aggravation of HBV-related ACLF.